Taxonomic review of the genus Urostylis (Hemiptera: Heteroptera: Urostylididae) from the Korean Peninsula, with description of a new species - Kim, Junggon; Roca-Cusachs, Marcos; Jung, Sunghoon (Zootaxa, 2018)
The genus Urostylis is reviewed taxonomically with description of a new species Urostylis koreana sp. nov. from the Korean Peninsula. Descriptions, diagnoses and a key to the Korean Urostylis species are presented with photographs and illustrations.